Stable generation of orbital angular momentum mode with an all-fiber laser. (13th March 2020) - Zhang, Yimin; Li, Hongxun; Tao, Runxia; Fang, Wentan; Dong, Zhipeng; Dai, Chuansheng; Xu, Lixin; Gu, Chun; Chen, Wei; Zhu, Yonggang; Zhan, Qiwen; Yao, Peijun
Abstract: In this letter, an all-fiber laser that can generate stable OAM modes with topological charges of ±1 is demonstrated. A ring-core fiber designed in-house is used to reduce the crosstalk between OAM mode and other modes. A ring-core fiber-based long-period fiber grating (LPFG) and a fiber Bragg grating (FBG) are employed to select desired OAM mode. The coupling ratio of LPFG from HE11 mode to OAM mode exceeds 16 dB, and the mode purity of OAM mode is as high as 94.41%. This simple and compact fiber laser can be integrated into fiber-based OAM mode multiplexing optical communication system.